Anesthesiologists' Choice of Nutritional Therapy of Intensive Care Patients: A Survey Study - Ahmet Şen; Başar Erdivanlı; Tolga Koyuncu; Abdullah Özdemir; Hızır Kazdal (Galenos Yayinevi, 2015)
Objective: Providing adequate nutrition to critical patients as early as possible following internalization is important. Hospitalized patients are among the highest risk groups for malnutrition. Material and Method: A questionnaire including 21 questions about clinician's demographics and nutritional therapies in intensive care units was e-mailed to anesthesiologists only. Partially answered questionnaires were not included in the analysis. Results: A total of 121 questionnaires were analyzed. Every three out of four clinician reported application of nutritional therapy in intensive care unit, and according to the guidelines. While 75% of the clinicians following the guidelines were routinely evaluating nutritional status of their patients, this ratio was only 19% in clinicians not following the guidelines (p=0.0003). Enteral nutrition was the first choice of all clinicians, and majority of the clinicians (90, 74.4%) preferred central venous catheter for parenteral nutrition. The most important criteria for the choice of parenteral nutritional solution were reported as calories per volume and presence of the solution at the hospital by all clinicians. Among the clinicians following the guidelines, 70% were administering fish oil, 95% were administering glutamin to their patients. Among the clinicians not following the guidelines, these ratios were 44% and 80%, respectively (p=0.01 and 0.02). Conclusion: We are in opinion that following the guidelines instead of the clinician's individual forecasts may improve the nutritional therapy.